2017
DOI: 10.1096/fj.201601282r
|View full text |Cite
|
Sign up to set email alerts
|

Adaptable interaction between aquaporin‐1 and band 3 reveals a potential role of water channel in blood CO2transport

Abstract: Human CO respiration requires rapid conversion between CO and HCO Carbonic anhydrase II facilitates this reversible reaction inside red blood cells, and band 3 [anion exchanger 1 (AE1)] provides a passage for HCO flux across the cell membrane. These 2 proteins are core components of the CO transport metabolon. Intracellular HO is necessary for CO/HCO conversion. However, abundantly expressed aquaporin 1 (AQP1) in erythrocytes is thought not to be part of band 3 complexes or the CO transport metabolon. To solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Importantly, interaction between B3p and AQP1 was adaptable to changes in membrane tonicity, which suggests that AQP1 involvement in response to tonicity could be associated with its function in B3p-mediated exchange. For this reason, AQP1 seems to be critically implicated in blood CO 2 transport and, in turn, respiration [16]. Their primary function is to allow tissue oxygenation and CO 2 elimination, but erythrocytes, flowing in the blood stream, make tissue oxygenation effective due to their biconcave shape, which corresponds to a greater area available for gas exchange and, notably, lets them adapt to the narrow capillaries.…”
Section: Role Of Band 3 Protein In Erythrocytesmentioning
confidence: 99%
“…Importantly, interaction between B3p and AQP1 was adaptable to changes in membrane tonicity, which suggests that AQP1 involvement in response to tonicity could be associated with its function in B3p-mediated exchange. For this reason, AQP1 seems to be critically implicated in blood CO 2 transport and, in turn, respiration [16]. Their primary function is to allow tissue oxygenation and CO 2 elimination, but erythrocytes, flowing in the blood stream, make tissue oxygenation effective due to their biconcave shape, which corresponds to a greater area available for gas exchange and, notably, lets them adapt to the narrow capillaries.…”
Section: Role Of Band 3 Protein In Erythrocytesmentioning
confidence: 99%
“…The estimated rate of HCO 3 − /Cl − exchange by erythrocytes of blood passed through the human lung corresponds to the rate of oxygen consumption of a human body . The importance of this theme is supported by known publications . For example, it was reported that in the case of hypoxia the amount of active CDB3 per erythrocyte of asphyxiated neonates was decreased in comparison with healthy newborns.…”
Section: Discussionmentioning
confidence: 81%
“…Most (> 90%) of the carbon dioxide inside and outside erythrocytes in blood is converted to anions HCO 3 − (the enzyme carbonic anhydrase accelerates this reaction) ( (55). The importance of this theme is supported by known publications (8,(56)(57)(58)(59)(60)(61). For example, it was reported (57) that in the case of hypoxia the amount of active CDB3 per erythrocyte of asphyxiated neonates was decreased in comparison with healthy newborns.…”
Section: Discussionmentioning
confidence: 96%
“…Though their interaction is more obvious in GP.Mur RBCs, AQP1-band 3 interaction also exists in RBCs lacking GP.Mur. Importantly, this AQP1-band 3 interaction could be dissipated by hypotonic conditioning (e.g., by diluting the physiological buffer HBSS with water to ∼250 mOsm/Kg) ( Hsu et al, 2017 ). This osmotically sensitive interaction between AQP1 and band 3 conceivably allows erythrocytes to sense and respond to hemodynamic shear stress, as well as changes of erythrocyte volume and shape during circulation.…”
Section: Osmotically Sensitive Interaction Between Aqp1 and Bandmentioning
confidence: 99%
“…Conceivably, membrane-bound, mobile AQP1 and cytosolic CAII may preferentially interact with one or more types of the band 3 complexes, resulting in structurally and functionally differentiable complexes on the erythrocyte membrane. Very likely the population of cytoskeleton-independent band 3 preferentially interacts with AQP1, as the protein-protein interaction between AQP1 and band 3 was measured by FLIM-FRET using inside-out vesicles (IOVs) from erythrocyte membrane that were depleted of much spectrin cytoskeleton and non-integral membrane-bound proteins ( Hsu et al, 2017 ). Additionally, as AQP1-band 3 interaction is adaptable to osmotic changes ( Hsu et al, 2017 ), it is possible that the interaction between CAII and band 3 could also be transitory and sensitive to osmotic or hemodynamic shear stresses ( Lazaro et al, 2014 ).…”
Section: Revisit the Model—“co 2 -Transport Metabomentioning
confidence: 99%